Positive regulation of the pts operon of Escherichia coli: genetic evidence for a signal transduction mechanism. - De Reuse, H (1991)
The pts operon of Escherichia coli is composed of the genes ptsH, ptsI, and crr, which code for three proteins of the phosphoenolpyruvate-dependent phosphotransferase system (PTS): the HPr, enzyme I (EI), and EIIIGlc proteins, respectively. These three genes are organized in a complex operon in which the major part of expression of the distal gene, crr, is initiated from a promoter region within ptsI. Expression from the promoter region of the ptsH and ptsI genes has been studied in vivo by using gene fusions with lacZ. Transcription from this promoter region is under the positive control of catabolite activator protein (CAP)-cyclic AMP (cAMP) and is also enhanced during growth in the presence of glucose (a PTS substrate). This report describes a genetic characterization of the mechanism by which growth on glucose causes transcriptional stimulation of the pts operon. This regulation is dependent on transport through the glucose-specific permease of the PTS, EIIGlc. Our results strongly suggest that transcriptional regulation of the pts operon is the consequence of an increase in the level of unphosphorylated EIIGlc which is produced during glucose transport. Furthermore, overproduction of EIIGlc in the absence of transport was found to stimulate expression of the pts operon. We also observed that CAP-cAMP could cause stimulation independently of the EIIGlc and that glucose could activate in the absence of cAMP in a strain overproducing EIIGlc. Our results indicate that glucose acts like an environmental signal through a mechanism of signal transduction. A sequence similarity between the C terminus of EIIGlc and the consensus of transmitter modules of the sensor proteins defined by E. C. Kofoid and J. S. Parkinson (Proc. Natl. Acad. Sci. USA 85:4981-4985, 1988) suggests that EIIGlc might have properties in common with the sensors of the two-component systems.